Predictors of Self-Care Behaviors in Heart Failure Patients: A Cross-Sectional Study - Moaddab, Fatemeh; Ghanbari, Atefeh; Salari, Arsalan; Kazemnezhad Leyli, Ehsan; Sedghi sabet, Mitra (Advances in Nursing & Midwifery, 2020)
Abstract Introduction: Adherence to self-care behaviors and determining its related factors in patients with chronic illnesses are mandatory. The objective of the present study was two-fold: first, to examine the self-care behaviors adherence among heart failure patients and second, to determine its predictors in a comprehensive study of various factors in patients with heart failure. Methods: This descriptive cross-sectional study was conducted on 239 patients with heart failure referred to Dr.Heshmat hospital as the only heart center in Guilan province (Northern Iran). The consecutive sampling method was used. Data were collected by Self-Care Heart Failure Index, Cardiac Depression Scale, Mini-Mental State Examination, and Charlson Comorbidity Index and were analyzed by descriptive statistics and analytical statistics in SPSS. Results: Results showed educational level, history of receiving information, and cognitive function as predictors of self-care maintenance. Also, monthly income, history of receiving information, and ventricular dysfunction were predictors of self-care management. Monthly income, admission status, number of hospitalizations, history of receiving information, and cognitive function are mentioned as predictors of self-confidence. Predictors of total self-care were monthly income, history of receiving information, and cognitive function. (P . 0.05). Conclusions: Promoting self-care behaviors could prevent the adverse effects of diseases such as readmission, prolonged hospitalization, and bed occupancy ratio. The majority of the participants had non-adherent self-care, and, according to the results, it is recommended that assessing predictors in these patients and planning. Also, it is suggested that more observational, qualitative, and mixed-method studies be done in the future.